Physiological Features of the Reproductive System of Female Nutria - Mironova, Lyudmila; Pavlenko, Olga; Bashkatova, Nelly; Burov, Sergey; Ortyakova , Irina (KnE Life Sciences, 2021)
This article provides information about a promising alternative field of animal husbandry – nutria breeding. This involves the production of fur and high-quality meat products, which contain a large amount of nitrogenous extractives and muscle hemoglobin. This study examined the sexual system of female nutria, and the dynamics, duration and features of each stage of the female nutria’s sexual cycle, including estrus, sexual arousal, hunting, braking and phase balancing. The methods of observation, clinical examination, research of smears and fingerprints, and analysis of the cytogram of the vaginal epithelium at different stages of sexual and physiological maturity of female nutria were used. When analyzing the cytogram of the vaginal epithelium, the structure, color, and percentage of basal, parabasal, superficial, and keratinized cells were indicated. Information about the timing of sexual and physiological maturity, their features, processes and signs of manifestation, and different timing of sexual and physiological maturity in summer and winter is provided. Keywords: nutria, female, puberty, physiological maturity